INTERNALISASI NILAI PENDIDIKAN KARAKTER FILM ANIMASI RIKO THE SERIES PADA SISWA KELAS V SD N GEMAH SEMARANG - Kharisma Cahyani Usmawati; Rofian; Kiswoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the representation of character education values in the animated film Riko The Series and to explain the internalization process of these values among fifth-grade students at SDN Gemah Semarang. The research is based on the importance of strengthening character education in primary schools through contextual, engaging, and easily understood media. Local animated films rich in moral messages are considered potential alternatives to support character-based learning.The study uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. Sources of data include selected episodes of Riko The Series (episodes 3–5, Season 5), classroom teachers, and students. Data were analyzed inductively through data reduction, data display, and conclusion drawing.The findings indicate that the film represents character values such as honesty, responsibility, discipline, cooperation, empathy, social care, and religiosity through narratives and visuals that are relatable to children’s experiences. The internalization process occurs through film viewing sessions followed by classroom discussions, reflective activities, and teacher-led reinforcement. Students demonstrated good understanding and positive responses toward the use of visual media in learning.In conclusion, the representation of values in this film makes it an effective medium for character education, particularly in elementary school settings. The internalization process becomes more optimal when supported by continuous teacher guidance. Recommendations are addressed to teachers, students, and schools to better integrate educational films into character education strategies.